2015
DOI: 10.4414/smw.2015.14169
|View full text |Cite
|
Sign up to set email alerts
|

Back to work? Socioeconomic status after kidney transplantation

Abstract: The employment rate in this Swiss cohort before and after successful kidney transplantation is high compared with the literature. A high number of living donors, of pre-emptive transplantations, and short dialysis vintages contribute to this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 21 publications
8
40
2
Order By: Relevance
“…We found less kidney transplanted patients working post-Tx than before, a finding in agreement with Nour et al [16] and Tzvetanov et al [23], but in opposition to a recent Swiss study [9] that reported more kidney transplanted patients working post-Tx (71%) than before. The latter study is a retrospective monocentric survey with a response rate of 55% and may, therefore, have overestimated employment status due to a possible selection bias.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found less kidney transplanted patients working post-Tx than before, a finding in agreement with Nour et al [16] and Tzvetanov et al [23], but in opposition to a recent Swiss study [9] that reported more kidney transplanted patients working post-Tx (71%) than before. The latter study is a retrospective monocentric survey with a response rate of 55% and may, therefore, have overestimated employment status due to a possible selection bias.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with most return to work studies taking pre-Tx employment status into account [47, 911], pre-Tx employment was the strongest predictor for post-Tx employment. 81% of the patients who were employed pre-Tx were employed 12 month post-Tx, versus 18% of those who were not employed pre-Tx.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations